Association of Wearable Activity Monitors and Digital Drainage Device With Daily Ambulation and Length of Stay Among Pulmonary Resection Patients: A Prospective, Randomized Controlled Study - Tzu‐Yi Yang; Ching‐Yang Wu; Ming‐Ju Hsieh; Yin‐Kai Chao; Ching‐Feng Wu (Thoracic Cancer, 2025)
ABSTRACT Background With advancements in medical devices, more hospitals are incorporating the digital chest drainage (DCD) system into postoperative care. Although some studies have suggested that the DCD system provides accurate information and shortens hospital stays compared with the traditional chest drainage (TCD) system, the effect of the DCD system on quality of life remains unclear. This study investigated whether the digital chest drainage system improves postoperative outcomes and quality of life. Methods This single‐center, prospective, randomized controlled trial initially included 362 patients. After exclusion and randomization, 128 and 125 patients were included in the DCD and TCD groups, respectively. Wearable devices were used to measure sleep duration and walking distance after surgery. Primary outcomes included postoperative recovery and quality of sleep and rehabilitation. Results Both groups had similar baseline characteristics. In terms of postoperative outcomes, the DCG group had shorter durations of chest tube insertion and hospital stays than the TCD group did. We noted no significant differences in postoperative pulmonary complications or extended hospitalizations exceeding 1 week between the groups. Regarding physiological changes, the DCD group had a longer sleep duration during the first 2 days after surgery. Furthermore, the number of walking steps after surgery was higher in the DCD group. Conclusion The DCD system provides precise information that can help surgeons in decision‐making, potentially shortening the postoperative course and reducing the need for postoperative chest x‐rays. Furthermore, the DCD system can enhance postoperative recovery by improving sleep quality and ambulation.